Interposition GraftJacket allografts for irreparable rotator cuff tears. (3rd January 2022) - Modi, Amit; Haque, Aziz; Deore, Vijay; Singh, Harvinder Pal; Pandey, Radhakant
Abstract : Aims: Long-term outcomes following the use of human dermal allografts in the treatment of symptomatic irreparable rotator cuff tears are not known. The aim of this study was to evaluate these outcomes, and to investigate whether this would be a good form of treatment in young patients in whom a reverse shoulder arthroplasty should ideally be avoided. Methods: This prospective study included 47 shoulders in 45 patients who underwent an open reconstruction of the rotator cuff using an interposition GraftJacket allograft to bridge irreparable cuff tears, between January 2007 and November 2011. The Oxford Shoulder Score (OSS), pain score, and range of motion (ROM) were recorded preoperatively and at one year and a mean of 9.1 years (7.0 to 12.5) postoperatively. Results: There was significant improvement in the mean OSS from 24.7 (SD 5.4) preoperatively to 42.0 (SD 6.3) at one year, and this improvement was maintained at 9.1 years (p < 0.001), with a score of 42.8 (SD 6.8). Similar significant improvements in the pain score were seen and maintained at the final follow-up from 6.1 (SD 1.6) to 2.1 (SD 2.3) (p < 0.001). There were also significant improvements in the ROM of the shoulder, and patient satisfaction was high. Conclusion: The use of an interposition human dermal allograft in patients with an irreparable rotator cuff tear leads to good outcomes that are maintained at a mean of nine years postoperatively. Cite this article: Bone Joint J  2022;104-B(1):91–96.